Iontophoretic Drug Delivery for the Treatment of Scars. Issue 6 (19th March 2014) - Manda, Prashanth; Angamuthu, Muralikrishnan; Hiremath, Shobharani R.; Raman, Vijayasankar; Murthy, S. Narasimha
<x xml:space="preserve">Abstract</x> Topical treatment of hypertrophic scars is challenging because of poor penetrability of drugs into the scar tissue. The objective of the study was to investigate the effectiveness of iontophoresis to deliver medicaments across the scar epidermis. Initially, biophysical studies were performed to investigate the differences between scar and normal skin epidermis obtained from cadaver. In case of scar skin epidermis, the transepidermal water loss was not significantly different from the normal skin epidermis, whereas the electrical resistivity was significantly higher. The passive permeation flux of sodium fluorescein was approximately one‐third of that across the normal skin epidermis. Scanning electron microscopy studies revealed that the two membranes were alike except that the scar skin epidermis lacked follicles. Cathodal iontophoresis enhanced the delivery of sodium fluorescein across the scar skin epidermis by approximately 46 folds [51.90 ± 8.82 ng/(cm2 h)]. However, the transport of sodium fluorescein across the scar skin epidermis was about an order of magnitude less than the normal skin epidermis. Overall, the studies suggest that iontophoresis could be utilized to overcome the barrier resistance of scar skin epidermis and treat the scar regionally. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci